Assessment of Diversity within the Nigeria Power Generation Technologies (Nigerian Journal of Technology, 2021)
The protracted imbalance and shortage in electricity supply in Nigeria has being adjudged to be multidimensional: ranging from generation to billing, due to inability to diversify our power generation technologies away from hydro and gas. Thus, this paper attempts to assess the extent of diversification of power generation technologies within the industry. Shannon Wiener diversity index was adapted to measures the extent of energy diversity among current and potential power generation technologies available to Nigeria. The result revealed an index value less than 1.5 indicating that the current energy mix has not been fully diversified, while the cumulative energy diversity indices estimated was 0.6, 1.3, 1.7 and 2.0 for year 2015, 2020, 2025, and 2030 respectively. It is expected that the introduction of other conventional and renewable resources into the mix will increase diversity and boost supply.